2017
DOI: 10.3989/scimar.04637.26a
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of nitrous oxide in the Minho and Lima estuaries (Portugal)

Abstract: Summary:Nitrous oxide (N 2 O) is a potent long-lived greenhouse gas and estuaries represent potentially important sources of this biogas to the atmosphere. In this work, we analyse the first N 2 O data obtained in the Minho and Lima estuaries, and the processes and environmental factors that may regulate its production in these systems. In Variabilidad espacial del óxido nitroso en los estuarios del Miño y Lima (Portugal)Resumen: El óxido nitroso es un poderoso gas de efecto invernadero y los estuarios repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In both seasons, the N 2 O load from freshwater input is high enough to more than account for all of the emitted N 2 O ( Figure 5) and in-situ production is not needed to explain the observed patterns. In some estuaries and 415 coastal waters, a positive correlation between N 2 O and apparent oxygen utilization has been interpreted as a sign of in-situ nitrification (Nevison et al, 2003;Goncalves and Brogueira, 2017), however this correlation was not observed in the Johnstone (Figure A2a,b), and neither did we observe a negative correlation between N 2 O and NH + 4 (Figure 8b), as would be expected if nitrification were 420 consuming large quantities of NH + 4 . Another possible pathway of N 2 O production or consumption is denitrification.…”
Section: Fitzroy River Estuary 320mentioning
confidence: 64%
“…In both seasons, the N 2 O load from freshwater input is high enough to more than account for all of the emitted N 2 O ( Figure 5) and in-situ production is not needed to explain the observed patterns. In some estuaries and 415 coastal waters, a positive correlation between N 2 O and apparent oxygen utilization has been interpreted as a sign of in-situ nitrification (Nevison et al, 2003;Goncalves and Brogueira, 2017), however this correlation was not observed in the Johnstone (Figure A2a,b), and neither did we observe a negative correlation between N 2 O and NH + 4 (Figure 8b), as would be expected if nitrification were 420 consuming large quantities of NH + 4 . Another possible pathway of N 2 O production or consumption is denitrification.…”
Section: Fitzroy River Estuary 320mentioning
confidence: 64%